EXPLAINING LOCAL ECONOMIC POTENTIALS BY USING SECTORAL AGGREGATIONS AND RURAL DEVELOPMENT - Dincer, Iclal (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
It is expected that regional development policies provide national development, and also decrease the gap between development level of each regions and urban-rural areas. However, it hasn't been reduce this unbalanced development among the regions although regional development policies are built up with this approach. Nowadays, the development projects on rural areas are getting more and more important. In this regard, experiences and attempts of European Union are based on rural development, rural regeneration, rural renaissance etc. and gives priority to the development of rural economy. Meanwhile, in the 9(th) National Development Plan, it is espoused to take measures which change according to the problems and the potentials of the regions in Turkey. In this frame, the aim of this paper, to introduce local potential of the regions and to define aggregations of rural settlements on the four main sectors - agriculture, industry, service, and commerce-in 1990. Aggregations of sectors are an important tool to regenerate local economy. In this regard, main objectives; aggregations of manufacturing industry, commercial and service sectors are the engine of economy in the rural areas of shore provinces in Mediterranean, Marmara and Aegean Sea. On the other side, it is not only agriculture but also service sector is the engine of the economy in Eastern Anatolia.
Keywords: rural development; unbalanced development; sectoral aggregation; Architecture